Identification and Academic Assessment Models for Students with Specific Learning Difficulties in Inclusive Elementary Schools - Ibnu Syamsi; Dwitya Sobat Ady Dharma (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
This study aims to identify students with special learning difficulties in inclusive primary schools and develop assessment models. The research subjects were inclusive elementary school students in Sleman Regency. Methods of collecting data were observation, tests, interviews, and surveys. The results showed that 85 students (18.27%) were identified as having certain learning difficulties. Male students have more specific learning difficulties than female students (55.3%: 44.7%). Specific learning difficulties were found in reading (26 students or 22.10%); in writing (23 students or 19.55%); and in mathematics (36 students or 30.60%). In assessing difficulties in writing, the researchers applied the practice of handwriting (beginner writing), spelling, and expressive writing. Informal and formal assessments were used to identify mathematical difficulties.